Double penile fracture with complete urethral disruption following anal intercourse: a case report - Barua, Sasanka K.; Pratihar, Sarbartha Kumar; T. P., Rajeev; Baruah, Saumar J.; Bagchi, Puskal K.; Sarma, Debanga; Phukan, Mandeep; Saurabh, Nikhil (International Surgery Journal, 2019)
Penile fracture remains a rare, under reported condition. It is defined as blunt trauma resulting in tear of tunica albuginea surrounding the corpus cavernosum during erection. Prompt diagnosis and early surgical repair are essential. Here we report a case of 37 years male with penile fracture involving both corpora cavernosum and complete urethral disruption. A 37-year-old man presented with penile injury during anal intercourse. Physical examination revealed a swollen, ecchymotic penis with dorsal angulation. Penile ultrasound showed tear in bilateral corpora cavernosa at ventral aspect with hematoma. On exploration tear in bilateral corpora with complete penile urethral disruption seen. Repair of corporal tear with end to end anastomotic urethroplasty done. He has normal voiding and sexual function at 4th months of follow up. The diagnosis of this condition is clinical, which is further augmented by high frequency sonography, which can detect exact site of the tear, also allows evaluation of penile vascularity. Evaluation of the urethra with sonography can help identify interruption of the urethral wall. As in our patient, double fracture involving corpora cavesnosa of both sides with complete urethral disruption, is rare entity. Urgent surgery with complete penile degloving is advocated and extreme care is needed not to miss any injury. Fracture of the penis is a rare surgical emergency. The diagnosis is clinical, however high-resolution sonography and colour Doppler are helpful. Early and prompt surgical intervention can restore normal voiding and erectile function to lead a healthy life.